Reshaping the Lower Face Using Injectable Fillers - Braz, André; Eduardo, Camila Cazerta de Paula (Indian Journal of Plastic Surgery, 2020)
The lower third is very important for the pleasant appearance of the face. A well-contoured jawline is desirable in men and women, giving a perception of beauty and youth. It is also key to sexual dimorphism, defining masculine and feminine characteristics. The nonsurgical rejuvenation and beautification of the lower third of the face is becoming more frequent. Injectable fillers can reshape the jawline, lift soft tissues, and improve facial proportions, effectively improving the appearance of the area.It is paramount to understand the facial anatomy and perform a good facial assessment in order to propose a proper aesthetic treatment plan. The aesthetic goal of the rejuvenation approach is to redefine the mandibular angle and line. In young patients, beautification can be achieved through correction of constitutional deficit or enhancement of the contour of the face, improving the facial shape. It is very important to possess knowledge of facial anatomy and of the aging process in order to deliver effective and safe results.In this article, we discuss the anatomy of the lower third of the face, facial assessment, aging process, and treatments of the chin, prejowls and mandibular line and angle with injectable fillers. The authors’ experience in the approach of this area is discussed.
Keywords: cosmetic therapies; dermal filler; facial rejuvenation; hyaluronic acid and calcium hydroxylapatite; lower face; nonsurgical